Modelling the Distributional Effects of the Cost-of-Living Crisis in Turkey and the South Caucasus: A Microsimulation Analysis - Zeynep Gizem Can; Cathal O'Donoghue; Denisa Maria Sologon; Darius Smith; Rosaleen Griffin; Una Murray (Institute of Labor Economics (IZA), 2023)
This study addresses the different distributional and welfare implications of price volatility amid the ongoing cost-of-living crisis, focusing on both Turkey and the South Caucasus region, which have different welfare regimes and patterns of price changes. This paper explores the impact of inflation and uses compensating variations and equivalized incomes to measure shifts in welfare in a cross-country comparative context. The effects of inflation are closely related to specific price increases for various goods and the distribution of household budgets. In particular, lower-income countries and individuals allocate a higher share of their budgets to essential goods such as food, heating oil, and electricity. Consequently, the pronounced price escalation in these essential goods has led to a stronger inflationary effect in the less affluent countries. Consistent with media narrative, we find that the distributional consequences of these price changes are more pronounced than originally thought. Nevertheless, there are notable differences across countries in the level of inflation, its composition, and the relative increase within the income spectrum. It is worth noting that comparable levels of inflation regressivity are due to different interactions between the magnitude of price inflation and its disproportionate impact on the income distribution. Our analysis quantifies the offsetting fluctuations associated with inflation and reveals a significant behavioural component, largely due to the fact that those exposed to significant price fluctuations predominantly purchase necessities. An important aspect to consider in the potential impact on households is the savings rate. Households with lower savings are disproportionately affected by these shifts in spending behaviour.
Keywords: E21; D12; D31; I30; 330; inflation; distributional effect; welfare effect